Case Report : Lymphocytic Lobulitis With Fibrocystic Disease Of The Breast: Life Sciences-General surgery - Tannistha Chakraborty; Dr. Shreya Shetty; Dr. K.S Ravishankar (International Journal of Life Science and Pharma Research, 2022)
Lymphocytic lobulitis , is a fibroinflammatory benign condition of the breast which is associated with type 1 diabetes mellitus. This benign condition is uncommon and may be mistaken for inflammatory carcinoma of the breast. We report the case of a 61 year old female patient who presented with a lump in the right breast with a history of Type 2 diabetes mellitus. The lump was associated with discharge and recent onset pain. On examination a vague lump which was non mobile, involving the right breast was palpable. A single firm mobile right axillary lymph node was palpable. Peau d’orange or orange peel appearance which occurs due to blockage of sub dermal lymphatics by tumour infiltrates, was noted over the skin. Clinically the features were suggestive of inflammatory carcinoma. Mammogram suggested an inflammatory carcinoma. Ultrasound of the breast was suggestive of right duct ectasia and diffusely thickened breast with a Breast Imaging Radiology and Data System (BIRADS) score of 3. An incision biopsy was performed with histopathology confirming the lesion as lymphocytic lobulitis with fibrocystic breast disease. The patient was symptomatically managed with analgesics and reassured. She was observed on regular follow up and is currently healthy. Lymphocytic lobulitis is a rare benign lesion which mimics carcinoma. Clinically it presents with ill defined single or multiple breast lumps in young or middle aged women with thickening and hardening of skin. Magnetic Resonance Imaging better differentiates this otherwise indolent lesion from malignancies. A histopathological examination is usually confirmatory and required to alleviate concerns of patients regarding presence of a malignancy which has a much fearsome physical and psychological implication.